The psychology of writing - Kellogg, Ronald Thomas (Oxford University Press, 1999)
The human ability to render meaning through symbolic media such as art, dance, music, and speech defines, in many ways, the uniqueness of our species. One symbolic medium in particular-written expression-has aroused increasing interest among researchers across disciplines, in areas as diverse as the humanities, education, and the social sciences because it offers a fascinating window into the processes underlying the creation and enunciation of symbolic representation. In The Psychology of Writing, cognitive psychologist Ronald T. Kellogg reviews and integrates the fast-growing, multidisciplinary field of composition research, a field that seeks to understand how people formulate and express their thoughts with the symbols of written text. By examining the production of written text, the book fills a large gap in cognitive psychology, which until now has focused on speech production, comprehension, and reading, while virtually ignoring how people write. Throughout, the author masterfully examines the many critical factors that come together during the writing process-including writer personality, work schedules, method of composing, and knowledge.; In providing an important new theoretical framework that enables readers from a wide range of backgrounds to navigate the extensive composition literature, the author drives home the profound significance of meaning-making as a defining feature of human cognition. Kellogg not only draws from the work of leading composition scholars, but quotes insights into the writing process proffered by some of the most gifted practitioners of the writing craft-including E.M. Forster, John Updike, and Samuel Johnson. Engaging and lively, The Psychology of Writing is the perfect introduction to the subject for students, researchers, journalists, and interested general readers.